Bridging Ethics and Ecology: Fiqh as a Framework for Sustainable Environmental Management - Mumun Munawaroh; Abdillah Syaikhon (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In recent years, the global discourse on environmental crises has intensified, driven by frequent natural disasters and ecological changes exacerbated by human actions. Islamic teachings, encapsulated in the Qur’an and Hadith, emphasize stewardship of the environment and prohibit actions that cause harm or corruption on Earth. This article explores the concept of environmental fiqh, known as fiqh al-bi'ah, which integrates Islamic jurisprudence with ecological principles to guide sustainable environmental management. It highlights the normative basis of environmental conservation rooted in Qur’anic verses and Prophetic traditions that underscore the interconnectedness of creation and humanity's role as stewards (khalifah). Fiqh al-bi'ah addresses issues such as cleanliness (thaharah), land reclamation (ihya al-mawat), and ecosystem protection (hima), aligning with the broader objectives (maqasid) of Islamic law. By elucidating these principles, this study underscores the ethical imperative of environmental preservation in Islam, offering a holistic framework to address contemporary environmental challenges and promote harmony between human activities and ecological integrity.